Distorções cognitivas e conflito conjugal na depressão pós-parto paterna - Koch, Sabrina (2014)
Depression is a general medical condition with a prevalence ranging between 4 % and 10 %. Postpartum depression is a specific manifestation of the disorder, affecting women and men. However, few studies address the issue of paternal postpartum depression. In this context, the present study aimed to investigate the effect of paternal postpartum depression on father-infant interaction, and the potential mediators effects (face processing, marital conflict and attention). To this end, two studies, one theoretical and one empirical. The theoretical study comprises a systematic review of the prevalence of postpartum depression in fathers and the impact on child development. Few studies related to the father-infant were found prevalence rates of paternal postpartum depression ranged between 1.2 % and 25.5 %. The empirical study, in turn, examined the effect of paternal postpartum depression on father- child interaction For this quantitative research design with two was performed. A total of 61 dyads father-infant (17 fathers with postpartum depression and 44 controls). Results confirmed the effect of postpartum depression on father-infant interaction. Face processing was confirmed as a mediator.